Single Crystal XRD Structure and Theoretical Analysis of the Chiral Au30S(S‑t‑Bu)18 Cluster - Crasto, David; Malola, Sami; Brosofsky, Grace; Dass, Amala; Häkkinen, Hannu (Journal of the American Chemical Society, 2014)
Au30S(S-t-Bu)18 cluster, related closely to the recently isolated “green gold” compound Au30(S-t-Bu)18, has been structurally solved via single-crystal XRD and analyzed by density functional theory calculations. The molecular protecting layer shows a combination of monomeric (RS-Au-SR) and trimeric (RS-Au-SR-Au-SR-Au-SR) gold–thiolate units, bridging thiolates, and a single sulfur (sulfide) in a novel μ3-coordinating position. The chiral gold core has a geometrical component that is identical to the core of the recently reported Au28(SPh-t-Bu)20. Both enantiomers of Au30S(S-t-Bu)18 are found in the crystal unit cell. The calculated CD spectrum bears a close resemblance to that of Au28(SPh-t-Bu)20. This is the first time when two structurally characterized thiol-stabilized gold clusters are found to have such closely related metal core structures and the results may increase understanding of the formation of gold clusters when stabilized by bulky thiolates.